Optimization of the Health and Safety Protocol for Covid-19 through the use of the QR Code in the Tailing Disposal System Project, Quellaveco - Moquegua, 2020 - Cristobal Coaguila Berly David,; Barriga Paria Christ Jesus, (International Journal of Engineering and Management Research, 2021)
The purpose of this research work is to optimize the occupational health and safety protocol by increasing distancing and mitigating physical contact to prevent the spread of Covid-19, using QR catches to identify personnel. Contrasting the sanitary measures to protect the health and integrity of the personnel of the operations area of the Tailing Disposal System -Quellaveco project. For the study of the database, factor analysis is used as a multivalent statistical method, with this method the number of 997 daily reports was analyzed, addressing the study of the structure of correlations between a large number of variables, factor analysis assists in the selection of a representative subgroup of variables and creates new variables called factors, when performing the analysis and treatment of 24 variables with the SPSS 25 software, the variables with the correlation matrix were reduced to 13, and with the total variance explained, a matrix different from that of identity was defined, reducing the dimensionality of the problem from 13 to 5 factors.